All-fiber integrated saturable absorber-tunable wavelength filter for Q-switching laser in both Cand L-bands - Kim, Byungjoo; Hong, Seongjin; Park, Jaedeok; Dong-Il, Yeom; Oh, Kyunghwan (Optics Express, 2021)
We proposed and experimentally demonstrated combining a nonlinear optic saturable absorber and a wideband-tunable spectral filter in a single graphene oxide (GO) film deposited fiber optic device. The GO film was prepared on the cleaved facet of an optical fiber applying two sequential processes: The electrical deposition to make a thick GO film using an arc fusion splicer, followed by the laser pulse drilling to form a multi-layered GO film. The GO deposited fiber facet and a pristine fiber facet formed an asymmetric Fabry-Perot interferometer (FPI), whose spectral response was flexibly controlled by adjusting the air gap between them. An all-fiber ring laser cavity was built using the proposed device as a tunable saturable absorber along with erbium-doped fiber as a gain medium in the L-band. Stable Q-switching laser pulse trains were successfully generated, whose pulse duration was in the order of a few microseconds and its peak wavelength was tunable over 40nm from 1564 to 1604nm covering both C-and L-bands. At a certain condition, we also obtained Q-switching pulses simultaneously lasing at the double wavelengths, 1573.3 and 1586.7nm. Detailed device fabrication processes and laser characteristics are described to elucidate the high potential of 2-dimensional material films in nonlinear optics.
Keywords: Device fabrications; Double wavelengths; Erbium doped fibers; Fiber-optic devices; Laser characteristics; Laser pulse train; Sequential process; Tunable wavelength filters